DETERMINING THE PERFORMANCE OF SHARIA COMMERCIAL BANKS WITH MODERATION OF NON PERFORMING FINANCING RATIO IN INDONESIA - Novan Wahyu Hidayat; Amalia Kusuma Wardini; Lela Nurlela Wati (Riset: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2021)
The research objectives to be achieved are: (1) To analyze and reveal empirically whether the Capital Adequacy Ratio (CAR), OE, Financing to Deposit Ratio (FDR), Net Operating Margin (NOM) affects the performance of Islamic Commercial Banks as measured by the ratio ROA). (2) To determine and analyze whether the non-performing loan ratio (NPF) moderates the effect of Capital Adequacy Ratio (CAR), OE, Financing to Deposit Ratio (FDR), and Net Operating Margin (NOM) on the performance of Islamic Commercial Banks (Return On Assets). This type of research is a quantitative research. The population used in this study is a Islamic commercial banks registered with the Financial Services Authority consisting of 14 BUS from 2015-2019. The data used is secondary data and uses saturated sampling method. Researchers used this sampling technique because the total population of 14 Islamic commercial banks companies in Indonesia are registered with the Financial Services Authority (OJK). Analysis of research data using Moderating Regression Analysis. Simultaneously CAR, OE, FDR and NOM have a positive effect on BUS performance for the 2015-2019 period as measured by ROA, but the partial results are only CAR that has a positive effect on ROA while OE, FDR and NOM have a negative effect on ROA, this happens because The capital adequacy held in the current period in lending is currently decreasing when compared to the previous period so that it has an impact on decreasing income and profit for the next period. Simultaneously, NPF moderates CAR, OE, FDR and NOM have a positive effect on BUS performance for the 2015-2019 period as measured by ROA, while the partial results are only NPF which has an impact on reducing the effect of CAR on ROA, while other variables when NPF moderate the relationship with ROA moves towards improvement. This is because the capital adequacy ratio is currently used in handling the current bad credit ratio as a result of loans extended in the previous period so that the current capital that should be used to generate profits in the next period through an increase in the volume of credit at this time from the previous period is reduced so that an impact on the decline in Islamic commercial banks profitability in the next period. As for what makes the difference in this study is the moderation of NPF on the effect of CAR, BOPO, FDR and NOM on ROA.